ANALISIS PENINGKATAN KEPATUHAN WAJIB PAJAK DALAM PEMBUATAN NPWP UKM DI KEBUN LADA KECAMATAN HINAI KABUPATEN LANGKAT - Rioni, Yunita Sari; Radhifan Syauqi, Teuku (Universitas Pembangunan Panca Budi, 2025)
The study aims to determine the level of compliance of taxpayers in making UKM NPWP in Lada Kebun Hinai District of Langkat Regency. The level of taxpayer compliance in making NPWP is very important because it can facilitate the UKM in the process of running their UKM. Data collection techniques used in this study were document data and interviews. Data analysis is done by comparing the level of taxpayer compliance in making UKM NPWP